A Study of Factors Affecting Consumers’ Purchase Intention on Buying Passenger Car among the Perspective of Malaysians - Soh, Pei Ting (2011)
In a highly competitive business environment, the understanding of purchase intention is important towards marketers. As a result, automobile manufacturer and assemblers ought to ascertain consumer purchase intention in order to stay ahead in the fierce competition and the globalization of the automobile industry. Despite prior studies on purchase intension, no framework has been analyzed nor discussed to identify consumers’ purchase intention. This research intends to fill this knowledge gap. Specifically, the purpose of this study is to explore Malaysian consumers’ perceptions with regards to their purchase intention on passenger cars; to identify how Country of Origin, informational influence, automobile attribute and service issues can effect on purchase intentions. By developing this knowledge, a proposed research framework is designed in order to present an in-depth understanding of identified variables on purchase intentions. The nature of the study is quantitative research with deductive approach. Self-administered questionnaire was conducted to 260 potential car buyers in selected five car companies in Malaysia in order to collect primary data. A quota sampling method was used to suit predetermined quota. A five-point Likert scale was used to measure respondents’ perceptions on intention to buy passenger car. Primary data analysis was generated with the use of SPSS 17.0. Reliability, validity, Independent sample t-test, Pearson Correlation and Multiple regressions were used to analyze the data of this research. The findings of this research have revealed that country of origin, informational influence, automobile attribute and service issues has significant effects on purchase intentions. In addition, the findings also showed that consumers have higher preferences to buy a foreign brand car instead of national brand car. Theoretical and practical implications are discussed with proper recommendations. Certainly, this research was able to draw vital information as a reference for future researches, government officials, and automobile manufacturers and dealers as proxy measures for Malaysian perceptions on car purchases. Future researches can expand the learning paradigm through the output of this study.